Potential Study of Organic Waste Residue Utilization at Garda Pangan to Reduce Landfill Disposal Burden: Kajian Potensi Pemanfaatan Residu Sampah Organik Garda Pangan Dalam Upaya Pengurangan Beban Pembuangan Ke TPA - Maryam Darlene Khoirunnisa R.; Muhammad Abdus Salam Jawwad (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2026)
Organic waste, particularly food waste, remains a major contributor to urban waste generation, and most of it ends up in landfills, thereby increasing the environmental burden. At the Garda Pangan Waste Management Facility, not all organic waste can be converted into maggot feed, resulting in residues characterized by a hard texture, large size, and high fiber content. This study aims to assess the potential for utilizing organic waste residues as an alternative for further processing to minimize the disposal burden on landfills. The methods used in this study include direct observation and comparative analysis of several bioconversion methods, such as eco-enzymes, vermicomposting, box composting systems, and livestock feed utilization. The results of the study indicate that the average weekly organic waste residue ranges from 360.17 to 785.12 kg, with a 35% increase from February to March 2026. Through the study, the box composting system was considered the most optimal because it can handle various types of waste with a reduction efficiency of 65–75% and is more suitable for the limited resource conditions in the field. Thus, this advanced treatment method has the potential to reduce the amount of organic waste disposed of at landfills.